Distance Education - Hriday Kant Dewan (Voices of Teachers and Teacher Educators, 2025)
The article discusses distance education and its role in a democratic society arguing that for democratic society possibility of continued learning is essential. This is not only required for educating stalls, opening avenues for professional careers but also participating in the democratic conversations in the society. The driving for a of open education cannot be degree and certification but to give people the confidence to learn what they want. It mentions the development of distance education and its gradual evolution in to a major possibility for continuing education particularly higher education. The paper clarifies the open and distance learning as a term and how the materials for these programs should be structured and what their nature including the language, style, exercise tasks and presentation should be. It underlines the importance of dialogue in the learning process and low open and distance learning programs can build that possibility. It subjects that careful use of ICT can help in making such programs qualitatively more engaging and meaningful.